The principles of Biblical interpretation : as enunciated by Irenaeus, Origen, Augustine, Luther, and Calvin - Wood, Arthur Skevington (Zondervan, 1967)
Now that we are passing, as many surmise, into the post-scientific period, is it possible to rethink this vitally relevant issue of interpretation, and to approximate more nearly to the mind of the Spirit? Certainly the question of interpretation has returned to the center of theological consideration today. It is being realized that what is technically known as the study of hermeneutics is an essential discipline for the biblical scholar.